Penyuluhan Manfaat Literasi Hukum Perpajakan dalam Mengembangkan UMKM di desa Panca Mukti - Marsidi, Marsidi; Afira, Annisa Putri; Sanjoyo, Riko; Wibowo, Budi; Reliati, Sance (Universitas Dehasen Bengkulu, 2021)
MSMEs are one of the contributors to the resilience of the national economy during the 1998 crisis and absorb a lot of informal labor, so they receive government attention and guidance, especially in the field of taxation. However, due to weak access to information by MSMEs, in general they do not necessarily understand and understand the benefits of fulfilling tax obligations, how and the methods that must be carried out in fulfilling them, and the risks that can be faced if MSMEs ignore the Government Regulation. MSME business actors in Panca Mukti Village are growing quite rapidly. Most of the businesses they are involved in are plantations, dairy cows, and home-based businesses such as shops, stalls, and food businesses. Nevertheless, their ability to manage finances is still very limited. Most of the business owners in Panca Mukti Village do not have financial records/reports, so they also do not have an NPWP and an understanding of taxes.